The Influence of Service Quality and Atmosphere on Customer Satisfaction at Cassiavera Restaurant Medan - Silitonga, Anisa Yulianti; Manurung, Aprina Septauli; Simandalahi, Eliata; Batubara, Nurul Khaira; Yani, Rindy Endry; Rahmadsyah, Agus (Economic: Journal Economic and Business, 2024)
The restaurant industry in Indonesia, especially in the city of Medan, has experienced rapid growth in recent years. Increasingly fierce competition encourages restaurant businesses to continue innovating to provide the best service to consumers. One of the factors that greatly influence customer satisfaction in the restaurant industry is the quality of service and the restaurant atmosphere. The aim of this study is to find out whether service quality and store atmosphere have an influence on customer satisfaction. The method used in this research is associative-causal. Collecting data through observation and interviews. The subject of this study are consumers at Cassiavera Restaurant Medan. The sampling technique used in this study is non-probability sampling. Data analysis shows that both service quality and atmosphere have a significant impact on consumer satisfaction. The results of this research provide important implications for restaurant management in efforts to increase customer satisfaction and organizational competitiveness